2011
DOI: 10.1134/s1560354711030051
|View full text |Cite
|
Sign up to set email alerts
|

On integrability of Hirota-Kimura type discretizations

Abstract: We give an overview of the integrability of the Hirota-Kimura discretization method applied to algebraically completely integrable (a.c.i.) systems with quadratic vector fields. Along with the description of the basic mechanism of integrability (Hirota-Kimura bases), we provide the reader with a fairly complete list of the currently available results for concrete a.c.i. systems.Comment: 47 pages, some minor change

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(149 citation statements)
references
References 27 publications
(68 reference statements)
6
136
0
1
Order By: Relevance
“…Some of the examples have required the use of relatively large computer memory space and computational time. In a forthcoming paper we will apply the method to a large variety of problems inspired by [6] and other literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the examples have required the use of relatively large computer memory space and computational time. In a forthcoming paper we will apply the method to a large variety of problems inspired by [6] and other literature.…”
Section: Discussionmentioning
confidence: 99%
“…In [7], we showed that any Hamiltonian systemẎ = J −1 ∇H in arbitrary dimensions, with constant symplectic structure, discretized by Kahan's method has one preserved modified measure and one modified integral which can be seen to coincide with (5) and with (6) respectively. However, the new algorithm presented here is more general as it can be also applied to systems which are not in the formẎ = J −1 ∇H and can be used to find all rational preserved integrals, given sufficient computing power (see Theorem 1).…”
Section: Example 1: Finding Measures and Integrals Of A 2d Hamiltoniamentioning
confidence: 99%
See 2 more Smart Citations
“…(i) No other method of the family (9) has a modified Hamiltonian when H is cubic, apart from the known cases a = 0, ± Our results are significant and novel for the study of both the integrability of the mappings produced by Kahan's method and for the study of the geometric properties of Runge-Kutta methods: • First, our results explain the integrability of the map obtained when Kahan's method is applied to some of the examples of [10]: their Eq.…”
Section: Discussionmentioning
confidence: 72%